Modeling and measurement of antenna characteristics of a satellite station based on software-defined radio - Baktybekov, K.S.; Ashurov, А.E.; Ivanov, А.V.; Kelgenbayev, А.Zh.; Zhapanova, А.S.; Sailaubaiuly, S. (Buketov Karaganda National Research University, 2025)
This study investigates the characteristics of a parabolic satellite antenna designed for communication with low Earth orbit satellites in the S-band. The choice of the S-band is motivated by the significantly lower power consumption of the radio link compared to the X-band. The S-band (2–4 GHz) is less sensitive to adverse weather effects than the X-band (8–12 GHz). These factors are critical for nanosatellites during Earth observation (EO) data transmission. Particular attention is given to measurements of the radiation pattern of the parabolic antenna in the S-band. These measurements provide essential data for optimizing the antenna design and parameters, thereby enhancing the overall efficiency of the communication system. During testing, both simulated and experimental radiation patterns of the gain were obtained, along with key antenna parameters such as Equivalent Isotopically Radiated Power, Input Power Flux Density, and the Gain-to-Noise Temperature Ratio. A comparison between measured and calculated results, including measurement accuracy and error budgets, demonstrated good agreement.
Keywords: radiation pattern; parabolic antenna; S-band; ground station; gain measurement; modeling